Cost Utility of Schlemm's Canal Microstent Injection With Cataract Surgery for Open-angle Glaucoma in the US Medicare System. Issue 6 (28th June 2022) - Atik, Alp; Rhodes, Lindsay A.; Samuels, Brian C.; Mennemeyer, Stephen T.; Girkin, Christopher A.
Abstract : Précis: Hydrus microstent (HMS) implantation at the time of cataract surgery appears to be cost-effective in mild-to-moderate glaucoma. However, long-term follow-up is essential for a full assessment of device performance, safety and cost-effectiveness. Purpose: The aim was to assess the societal cost-utility to the US Medicare system of implanting HMS with cataract surgery versus cataract surgery alone in patients with open-angle glaucoma. Patients: Markov model cohort of patients with mild-to-moderate open-angle glaucoma and visually significant cataract. Methods: Patients received HMS during cataract surgery versus cataract surgery alone, in a deterministic model over a 2-year horizon using TreeAge software. Both arms received additional ocular hypotensive agents to control intraocular pressure. Treatment effect of HMS was measured as mean number of ocular hypotensive medications and intraocular pressure, which directly impacted transition probabilities. Health states included the Hodapp-Parrish-Anderson glaucoma stages (mild, moderate, advanced, blind) and death. One-way sensitivity and probabilistic sensitivity analyses were conducted on device efficacy and longer time horizons. Results: At 2 years, HMS with cataract surgery in mild glaucoma had an incremental cost-utility ratio of USD 38, 346.43 per utility gained, compared with cataract surgery alone. Probabilistic sensitivity analysis was cost-effective in 61.4% of iterations for HMS+cataract surgery. The probability of side-effects with eye drops, utility decrement with side-effects, cost of the HMS and real-world efficacy rate had the greatest impact on model outcomes. HMS must be 85.60% as effective as published data to maintain cost-effectiveness at a willingness-to-pay threshold of USD 50, 000. The incremental cost-utility ratio of HMS with cataract surgery in moderate glaucoma was USD 42, 895.38. Conclusions: HMS implantation during cataract surgery appears to be cost-effective for patients with mild-to-moderate glaucoma. Nevertheless, more long-term safety and efficacy data are required.